Media Digital Padlet dan Socrative Sebagai Alternatif Pengembangan Pembelajaran Geometri - Arif Abdul Haqq; Adi Krisnanto; Darwan Darwan (Pusat Teknologi Informasi dan Pangkalan Data IAIN Syekh Nurjati Cirebon, 2021)
This research is motivated by the Covid – 19 pandemic problem and the need for teachers for learning media that can help in e – learning. The type of research used is research and development which adopt the development of Brog and Gall with 6 stages. The subject of this study were 21 students of class VIIIB there Plered public junior high school who were chosen by proposive sampling. The research design in the test was limited to the assessment phase using the ones group pretest-posttest design. The result of the research and development of the Padlet learning media showed good result, seen from the results of the experts’ assessment. Based on the pre – test and post – test results, the N – Gain value was 0,58 in the good category. The average result of each teacher’s responde to the media to determine the ease and feasilbility of obtaining 95,45% with the predicate was very good, so that the Padlet learning media was suitable for use by teachers in e – learning. The results of the students response obtained presentage on each aspect of the Padlet learning media of 88,92% with the predicate was very good.